Achieving improved electromagnetic interference shielding performance and balanced mechanical properties in polyketone nanocomposites via a composite MWCNTs carrier. (September 2020) - Yang, Yan; Feng, Changping; Zhou, Yichun; Zha, Xiangjun; Bao, Ruiying; Ke, Kai; Yang, Mingbo; Tan, Changbin; Yang, Wei
Abstract: A simple and scalable melt compounding strategy is reported to prepare polyketone (POK) nanocomposites with high electrical, dielectric, EMI SE and excellent mechanical properties using poly(vinylidene fluoride) (PVDF) as a carrier of MWCNTs based on the selective distribution and migration of MWCNTs in POK/PVDF blend. The electrical percolation threshold of the POK/PVDF/MWCNT nanocomposites is only a half of that of POK/MWCNT composites due to the homogeneous dispersion of MWCNTs and the double percolation network. The enhanced dielectric performance originates from the interfacial polarization and numerous microcapacitors comprised of MWCNTs within the polymer. The EMI SE performance of the nanocomposites is significantly enhanced due to the selective localization of MWCNTs in the POK phase which provides high conductivity and heterogeneous dielectric media with multiple interfaces. Thus, this study provides possibilities to realize a high-performance polymer nanocomposites and a wider EMI shielding application potentials for POK materials via a composite MWCNTs carrier.